Effects of a single postnatal methamphetamine administration on NMDA-induced seizures are sex- and prenatal exposure-specific - Slamberová, Romana; Schutová, Barbora; Matejovská, Iveta; Bernásková, Klára; Rokyta, Richard (Naunyn-Schmiedeberg's archives of pharmacology, 2009)
The aim of our study was to reveal whether acute methamphetamine (MA) administration changes the sensitivity to seizures induced by N-methyl-D-aspartate (NMDA) in prenatally MA-exposed adult rats. Adult rats with respect to sex and female estrous cycle (prenatally MA-exposed, prenatally saline-exposed, and controls) were divided into groups with acute MA (1 mg/kg) or without acute drug administration (saline injection). Intraperitoneal administration of 250 mg/kg of NMDA was used as a seizure model. The present study demonstrated that both prenatal MA and prenatal saline exposure decreased the latency to onset of stereotypy and clonic-tonic seizures. Acute MA administration decreased latency to onset of stereotypic behavior in all groups, while increased latency to onset of clonic-tonic seizures in prenatally saline-exposed rats. The duration of NMDA seizures was longer after acute MA administration relative to animals without acute MA pretreatment in both control groups. In addition, males displayed decreased susceptibility to NMDA-induced seizures relative to females regardless of their estrous cycle. Our study suggests that acute MA exposure changes susceptibility to NMDA-induced seizures in respect of prenatal exposure and sex. However, it seems that the effect of prenatal exposure is not induced by the drug per se but rather by the repeated injection exposure that causes prenatal stress.
Keywords: rozvrh dávkování léků; methamfetamin; Animals; Rats; Methamphetamine; Female; Estrous Cycle; Rats, Wistar; Seizures; N-Methylaspartate; ženské pohlaví; estrální cyklus; Time Factors; časové faktory; těhotenství; Drug Administration Schedule; zpožděný efekt prenatální expozice; Sex Factors; N-methylaspartát; Male; agonisté excitačních aminokyselin; sexuální faktory; Prenatal Exposure Delayed Effects; Excitatory Amino Acid Agonists; Stereotyped Behavior; stereotypní chování; krysa rodu Rattus; stimulanty centrálního nervového systému; zvířata; mužské pohlaví; Pregnancy; Central Nervous System Stimulants; záchvaty; potkani Wistar